2014
DOI: 10.1007/s11695-014-1536-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Lowest Weight and Long-Term Weight Regain Among Roux-en-Y Gastric Bypass Patients

Abstract: While weight nadir was associated with relatively few and largely nonmodifiable variables, WR was significantly associated with adherence-related behaviors, mood symptoms, and pathological patterns of food and alcohol use, all of which are potentially modifiable. These findings underscore the importance of long-term behavioral and psychosocial monitoring after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 48 publications
4
81
0
1
Order By: Relevance
“…This finding supports our hypothesis that steady state signifies a completed adaptation of the body to the physiologic mechanisms of weight loss produced by RYGB with little meaningful weight loss occurring beyond the SS period. This is strengthened by recent studies citing that weight regain, once reaching maximal weight loss, is likely due to poor lifestyle and dietary choices [15,16]. Therefore, patients should be counseled that any additional weight loss after steady state will likely be modest and similar in difficulty to that with traditional dieting.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports our hypothesis that steady state signifies a completed adaptation of the body to the physiologic mechanisms of weight loss produced by RYGB with little meaningful weight loss occurring beyond the SS period. This is strengthened by recent studies citing that weight regain, once reaching maximal weight loss, is likely due to poor lifestyle and dietary choices [15,16]. Therefore, patients should be counseled that any additional weight loss after steady state will likely be modest and similar in difficulty to that with traditional dieting.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in fat mass and VAT play an important role in decreasing the risk of cardiovascular disease and type-2-diabetes [1]. However, bariatric surgery alone may not mitigate the aforementioned comorbidities associated with obesity over the long-term as varying amounts of weight regain are commonly observed postsurgery [3].…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10] Contributing psychosocial factors to weight regain are varied and may include disinhibition of eating, grazing behavior (continuous snacking throughout the day), food cravings, poor well-being, poor self-concept, lack of planned exercise, not following aftercare recommendations, and social support. 6,[11][12][13][14] Disinhibition of eating may be an important factor leading to weight regain. 15 Disinhibition is the tendency to overeat in response to different stimuli, and can occur in a variety of circumstances such as when an individual is presented with a selection of appetizing foods in a social environment, is under emotional distress, or due to life's daily challenges.…”
Section: Introductionmentioning
confidence: 99%
“…17 Past and recent research notes the continuing lack of longterm follow-up to assess and support patients' well-being, especially when, at 18 months post-surgery, a significant portion of the bariatric population begins to regain weight. 8,11,14,[18][19][20][21] Moreover, Puzziferri et al 20 conducted a comprehensive review of 184 systematic reviews regarding bariatric surgery outcomes, and found that only three reviews reported studies of >5 years. In addition, none of the 184 reviews evaluated continuing post-surgery follow-up, and the researchers postulated that the efficacy of bariatric surgery was overestimated due to undocumented parameters regarding follow-up.…”
Section: Introductionmentioning
confidence: 99%